2017
DOI: 10.1590/1983-21252017v30n224rc
|View full text |Cite
|
Sign up to set email alerts
|

BUFFEL GRASS MORPHOAGRONOMIC CHARACTERIZATION FROM Cenchrus GERMPLASM ACTIVE BANK

Abstract: -This study aimed to characterize buffel grass accessions of the Cenchrus Germplasm Active Bank (CGAB) from Embrapa Semi-Arid in a morphoagronomic way, checking the descriptors variability and efficiency in accessions on two consecutive cuts. Twenty-five accessions and five buffel grass cultivars were used in randomized complete block design with three replications. Evaluations were conducted after two consecutive cuts, each evaluation performed 90 days after each cut. Characterization was based on 15 quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
0
4
0
3
Order By: Relevance
“…Early estimates of existing variability are obtained from the characterization of the genetic material, being one of the steps to access genetic diversity, both within and among plant accesses, since observations and measurements of several phenotypic descriptors are easily detectable (Burle & Oliveira, 2010). These results are then used in conjunction with other characterization techniques, such as DNA markers, cytogenetic techniques, among others (Bruno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Early estimates of existing variability are obtained from the characterization of the genetic material, being one of the steps to access genetic diversity, both within and among plant accesses, since observations and measurements of several phenotypic descriptors are easily detectable (Burle & Oliveira, 2010). These results are then used in conjunction with other characterization techniques, such as DNA markers, cytogenetic techniques, among others (Bruno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The accessions tended to be grouped by country of origin (Fig. 3 Bruno et al (2017) found significant morphological and agronomic differences between Cenchrus ciliaris accessions from the same country when evaluating 30 accessions of the same AGB, indicating high morphological variability of intra and interspecific regions, regardless of the country of origin.…”
Section: Discussionmentioning
confidence: 99%
“…accessions collected worldwide since 1970s. Some genotypes were evaluated regarding their morphological and agronomic traits (BRUNO et al, 2017), however, molecular tools were not used to screening the accessions of this collection. In this context, the objective of this work was to evaluate the genetic diversity of accessions of Cenchrus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar do potencial forrageiro das gramíneas nativas da Caatinga, o capim buffel (Cenchrus ciliaris L.), gramínea originária da África, Índia e Indonésia, amplamente cultivada em regiões tropicais e subtropicais em todo o mundo é uma planta perene, tolerante à seca, que apresenta alta resistência ao déficit hídrico, sendo uma das gramíneas forrageira mais adequada para o Semiárido brasileiro (Bruno et al, 2017;Moreira et al, 2015). Portanto, explorar seu germoplasma, ou de espécies do mesmo gênero, pode contribuir para a seleção de genótipos com potencial forrageiro, adaptados as condições climáticas regionais (Bruno et al, 2017).…”
Section: Melhoramento Genético Do Capim Buffelunclassified
“…Dentre as pesquisas realizadas no programa de melhoramento da cultura, destaca-se a caracterização agronômica de acessos (Bruno et al, 2017;Jorge et al, 2008;Moreira et al, 2015), com base na altura (Silva et al, 1987) e em análise bromatológica (Silva et al, 1987), além de estudos de diversidade genética (Burson et al, 2015), obtenção de genótipos sexuais para reprodução (Quiroga et al, 2013), determinação da ploidia de acessos por citometria de fluxo (Burson et al, 2012) e estudos de variabilidade morfogenética e ecotípica para resistência à seca no deserto de Cholistan, Paquistão (Arshad et al, 2007;Mansoor et al, 2002 Um dos fatores limitantes no programa de melhoramento da cultura é a reprodução da espécie, conhecida genericamente como apomixia. Neste tipo de reprodução, o embrião se desenvolve no ovário a partir de uma célula somática do óvulo, ocorrendo à formação de sementes férteis, sem haver a união do gameta feminino com o masculino, como ocorre na reprodução sexual (Gauer & Cavalli-Molina, 2000).…”
Section: Melhoramento Genético Do Capim Buffelunclassified